High-performance nickel sulfide modified electrode material from single-source precursor for energy storage application - Sambathkumar, C.; Ranjithkumar, R.; Arasi, S. Ezhil; Manikandan, A.; Nallamuthu, N.; Kumar, M. Krishna; Arivarasan, A.; Devendran, P. (Journal of materials science. Materials in electronics, 2021)
High-performance energy storage electrode materials are emerging demand in near future for the construction of supercapacitor with high energy and power densities. Herein, Nickel (II) Diethyldithiocarbamate was used as single-source precursor for Nickel Sulfide (Ni 9 S 8 ) two-dimensional (2D) nanosheets (NSs) preparation and hexadecylamine as shape directing agent via simple solvothermal method. The orthorhombic structure of Ni 9 S 8 NSs was confirmed by X-ray diffraction (XRD) pattern. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images revealed that as-prepared Ni 9 S 8 nanoparticles possess sheet-like morphology. Besides, the thermal stability of Ni(DTC) 2 complex was studied by Thermogravimetric/Derivative Thermogravimetric (TG/DTG) with differential scanning calorimetric (DSC) analysis. The electrochemical properties of Ni 9 S 8 NSs was studied using galvanostatic charge–discharge (GCD) and cyclic voltammetry (CV) techniques. From the charge–discharge study of Ni 9 S 8 NSs, a high specific capacitance of 281 Fg −1 was obtained at a current density of 1 Ag −1 and up to 82% retentivity was achieved after 5000 cycles. Thus, the prepared Ni 9 S 8 NSs could be the one of the attractive potential active electrode materials for the application of supercapacitor.